A conceptual risk management framework for post-closure settlement of fill - Brink, GE; Heymann, E (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Surface mining operations in the Pilbara typically lead to the disturbance of large areas of land over the life cycle of mines. Due to this disturbance, final landforms typically include large voids and waste rock landforms that commonly remain within the disturbance footprint in perpetuity. In Western Australia, the Department of Energy, Mines, Industry Regulation and Safety (DEMIRS) is responsible for regulating mining activities, including rehabilitation and closure. DEMIRS typically require at a minimum that all disturbed areas are rehabilitated and closed in a manner to make them physically safe to humans and animals, geotechnically stable, geochemically non-polluting/non-contaminating, and capable of sustaining an agreed post-mining land use without unacceptable liability to the state. To assist in achieving the desired outcomes (including increasingly stringent closure completion criteria set by stakeholders), waste material that would commonly sit within waste landforms is increasingly being utilised as backfill material to mined-out voids, and in some cases these landforms are constructed within the pit itself (in-pit dumps). The controlled placement[footnoteRef:3] of waste material is generally not considered feasible at open pit mines in the Pilbara. This is largely due to the scale of the operations (and therefore associated financial implications), variability in waste material properties, as well as the fact that most post-mining land uses in the Pilbara are not considered sensitive to ground settlement. The magnitude of settlement of unconsolidated waste materials in backfill and ex-pit waste landforms, which are often of substantial thicknesses, could however be pronounced. In addition, significant uncertainty surrounds the rate and duration over which settlement takes place; depending on the prevailing settlement component, material characteristics and other environmental factors (e.g. rise in groundwater levels). Such levels of change in the final surface level, if unaccounted for, are likely to have a significant impact on the as-built pit backfill and waste material landforms through the development of surface cracks, changes in the landform slope angle, development of preferential surface water flow paths and ponding. [3: Controlled placement refers to fill placed using a performance specification, a method specification or a thick layer specification] The long-term settlement characteristics of the waste material captured in these landforms therefore becomes an important consideration in ensuring the closure objectives are achieved and, most importantly, maintained post-closure. Very little information surrounding settlement behaviour of waste material in the Pilbara exists in the public domain and published literature. This paper is not intended as a detailed discourse on the mechanism of backfill settlement or the geotechnical assessment of the factors which govern it. The intent of this paper is rather to present a risk management framework (RMF) aimed at addressing the potential risk of post-closure settlement by considering the current paucity of technical, Pilbara-specific data on the topic of fill settlement. This RMF is intended to ultimately form part of a more comprehensive geotechnical and overall site rehab and closure risk management plan.
Keywords: waste material